Exploring fish consumption patterns and preference factors among consumers in the Siraha district of Nepal - Chaudhary, Balmiki; Yadav, Shubh Pravat Singh; Yadav, Bishnu; Chaudhary, Swastika; Magar, Keshab Kumar Budha; Sah, Sumit Kumar (Turkish Journal of Agriculture - Food Science and Technology, 2023)
Fish consumption choices are impacted by the socioeconomic aspects of customers. A field survey was done in 2022 with the purpose of (i) measuring the frequency of fish consumption, (ii) studying the socioeconomic characteristics of customers and their preferences; and (iii) researching the variables impacting the consumption of fish by consumers in the Siraha district. A sample size of 102 individuals was selected randomly from the Siraha district, including the Lahan Municipality, Dhangadhimai Municipality, and Golbazar Municipality, to ensure representation across diverse socio-economic backgrounds. Data was collected using a questionnaire administered to the participants. Respondents (58.8%) overwhelmingly prefer to eat fish more than twice a week, throughout the year or particularly in winter. Rohu (Labeo rohita) and carp (Cyprinus carpio) are the most often eaten fish species. The frequency of fish-consumption shows a strong connection with income level and education level. The stepwise multiple regression model explained 58.1% of the overall variation in fish consumption. The market structure is not sanitary, the price of fresh fish is expensive, and the consumption frequency of customers is impacted, particularly for poor socio-economic groups. boosted by a variety of various legislation, marketing, and advertising methods. In addition, consumers should be dispersed throughout the year rather than exclusively in particular seasons.